2000
DOI: 10.1080/01639620050085843
|View full text |Cite
|
Sign up to set email alerts
|

life in prison: perspectives of drug injectors

Abstract: Although there is a considerable literature on people's lives in prison, little is known about drug injectors inside prison. Drug injectors with prison experience were invited to discuss prison life during qualitative in-depth interviews and small group discussions. Drug injectors were recruited in the community in England and 24 people participated. Analysis of responses identiüed the following broad themes as important-entering prison and early experiences; prison conditions; prison regimes; days in the live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…However, many carry on using on the inside, often with reduced frequency and amounts [51], but sometimes maintaining the same level of use [52]. Prison is also a place where drug use is initiated, often as a means to release tension and to cope with being in an overcrowded and often violent environment [53,54]. …”
Section: Reviewmentioning
confidence: 99%
“…However, many carry on using on the inside, often with reduced frequency and amounts [51], but sometimes maintaining the same level of use [52]. Prison is also a place where drug use is initiated, often as a means to release tension and to cope with being in an overcrowded and often violent environment [53,54]. …”
Section: Reviewmentioning
confidence: 99%
“…Previous international qualitative studies have explored prisoners’ experiences in prison of which health was a major component. These studies explored prison life and the impact of imprisonment on health including the resultant loss of autonomy for self-care, enforced breaks from drugs and chaotic lifestyles and having more time on their hands to address overdue health needs (Hughes and Huby, 2000; Douglas et al , 2009; Maruca et al , 2017; Gately et al , 2006). The barriers to accessing health care identified, in studies evaluating prison health services include: long waiting times, delays and changes in medication, confidentiality breaches, poor communication, gatekeeping practices by staff, absence of information concerning health practices and medication and quality of health care (Ahmed et al , 2016; Bowen et al , 2009; Plugge et al , 2008; Russell et al , 2006; Sullivan et al , 2015; Condon et al , 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These reasons include frustrations associated with being incarcerated, family problems, and fatalistic attitudes because of long or life sentences. Although any inmate could engage in risk behaviors, inmates who had been incarcerated for long periods and those who were on life sentences were more likely to engage in sex and substance abuse [29] [30]. With regards to drug use, it has been "argued that confinement is a predictor of drug use" [12] and several studies have concluded that boredom, hopelessness, and frustration contribute in part to drug use [13] [20].…”
Section: Discussionmentioning
confidence: 99%